Group based access control scheme: Proof of method for secure access control architecture in mobile ad-hoc networks - Bakar A.A. (2023)
In disaster area, where the infrastructures is partially or fully destroyed, a form of communication to allow information been shared among rescue team is needed. Since Mobile ad-hoc network is easy to setup and required less infrastructure therefore it is a suitable candidate to work in disaster area. Despite of its uniqueness, this network is highly vulnerable to malicious node and also to threats. In rescue mission scenario, information needs to be shared among trusted and legal nodes only hence a mechanism to restrict an access to information in this network is extremely important. In this paper, we outline the access control requirement for this network and proposed the secure access control architecture based on the requirements. Based on the proposed architecture, we derive a Group Based access control scheme, to show how an access to information in mobile ad-hoc environment at emergency rescue mission is working. Copyright 2009 ACM.